2021
DOI: 10.47259/ijrebs.235
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the Financial Performance of Bank Dhofar

Abstract: Purpose: The aims of this research was to identify how COVID-19 had affected the financial performance of Bank Dhofar, to analyze the financial performance indicators, to evaluate how did Bank Dhofar react to the changes and to evaluate whether Bank Dhofar had taken right action take to mitigate potential financial performance damages. Design/methodology/approach: This research follows a descriptive analytics research method. The primary data was collected using a questionnaire. Samples were selected based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This is following the research conducted by [28] which provides information that firm ROA is negatively related to cumulative cases of COVID-19. Meanwhile, [51], [42], and [3] stated that COVID-19 had a negative effect on the firm's financial performance. [39] their research revealed that COVID-19 is detrimental to financial performance which is supported by the results of research by [16] and [21] who said that COVID-19 substantially affected financial overall performance due to the fact there's a sizable difference in financial overall performance between before and after COVID-19 took place.…”
Section: Coronavirus Disease Of 19 (Covid-19) On Financial Performancementioning
confidence: 99%
“…This is following the research conducted by [28] which provides information that firm ROA is negatively related to cumulative cases of COVID-19. Meanwhile, [51], [42], and [3] stated that COVID-19 had a negative effect on the firm's financial performance. [39] their research revealed that COVID-19 is detrimental to financial performance which is supported by the results of research by [16] and [21] who said that COVID-19 substantially affected financial overall performance due to the fact there's a sizable difference in financial overall performance between before and after COVID-19 took place.…”
Section: Coronavirus Disease Of 19 (Covid-19) On Financial Performancementioning
confidence: 99%